Employer BrandÄ±ng on Brand CÄ±tÄ±zenshÄ±p BehavÄ±or: ExplorÄ±ng the MedÄ±atÄ±on of Brand-Person FÄ±t and Brand CommÄ±tment - Safitri, Rini; Do, Ben Roy; Irawanto, Dodi Wirawan (APMBA (Asia Pacific Management and Business Application), 2017)
In the service industry, customer perception of the corporate brand is often based on the employee they interact with. Employer branding can be beneficial to attract and retain employees, as doing so can distinguish the company from competitors. Employer branding may also make the employee live with the brand, called brand citizenship behavior. Using data collected from employees of a largest telecommunication company in Indonesia, the present study explores the relationship between employer branding and brand citizenship behavior, with brand-person fit and brand commitment as possible mediators. Data was collected by online questionnaire and processed using Amos. Results show employer branding influences brand citizenship behavior either directly or indirectly through brand commitment, but not through brand-person fit.